New Insights into the Biological Role of Mammalian ADARs; the RNA Editing Proteins - Mannion, Niamh; Arieti, Fabiana; Gallo, Angela; Keegan, Liam P; O'Connell, Mary A (Biomolecules, 2015)
The ADAR proteins deaminate adenosine to inosine in double-stranded RNA which is one of the most abundant modifications present in mammalian RNA. Inosine can have a profound effect on the RNAs that are edited, not only changing the base-pairing properties, but can also result in recoding, as inosine behaves as if it were guanosine. In mammals there are three ADAR proteins and two ADAR-related proteins (ADAD) expressed. All have a very similar modular structure; however, both their expression and biological function differ significantly. Only two of the ADAR proteins have enzymatic activity. However, both ADAR and ADAD proteins possess the ability to bind double-strand RNA. Mutations in ADARs have been associated with many diseases ranging from cancer, innate immunity to neurological disorders. Here, we will discuss in detail the domain structure of mammalian ADARs, the effects of RNA editing, and the role of ADARs in human diseases.
Keywords: deaminase domain; savci; dvouvláknová RNA; proteiny vázající RNA; Humans; cancer; ADAR; lidé; zvířata; Mammals; Adenosine Deaminase; adenosindeaminasa; Alu elements; dsRBDs; editace RNA; RNA Editing; RNA, Double-Stranded; RNA editing; Animals; RNA-Binding Proteins